Making unbreakable code. - Mullins, J. (IEEE spectrum)
A product is on the way that relies on the quantum properties of photons to keep out eavesdroppers. All of them. The battle between codemakers and codebreakers is centuries old, but at the start of the 21st century, could it finally be drawing to a close? Physicists are putting the finishing touches to a method of encrypting messages that is more secure than anything that has gone before. Unlike the ciphers of the past, this new method has the potential to be absolutely unbreakable, not just practically unbreakable, but theoretically unbreakable. Mathematicians believe they can prove it. Central to the technique are the strange laws of quantum mechanics. Already experimental messages encrypted using quantum mechanics are being sent over tens of kilometers of optical fibers and received securely. Researchers are confident that it will not be long before ultra-secret messages are routinely transmitted in this way. But while quantum cryptography may be perfect in theory, practical considerations introduce security loopholes that an eavesdropper can exploit. The seriousness of these is still unclear, and physicists believe they can plug most of the holes with more efficient equipment. Still, enough cracks remain to maintain a healthy interest among cryptographers